Faktor – Faktor yang Mempengaruhi Integritas Laporan Keuangan pada Perusahaan Sektor Kesehatan di BEI 2023-2025 - Mahardika Hillary Dwinda Fatmawati; Maryono; Sri Sudarsi; Ali Maskur (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to examine and analyze the influence of institutional ownership, company size, leverage and audit quality on financial statement integrity. Method: The study used secondary data with a quantitative approach. The sampling technique used purposive sampling on 31 healthcare companies listed on IDX 2023 – 2025 period, resulting in 93 observations. Analysis was performed using multiple linier regression using IBM SPSS software. Finding: The result show that institusional ownership has a negative and significant effect on financial statement integrity. Company size has no significant effect, while leverage and audit quality have a positive and significant effect. Novelty: this study expands on previous research by adding company size an independent variable. Keywords: Financial statement integrity, institutional ownership, company size, leverage, audit quality.